2020
DOI: 10.1253/circj.cj-20-0402
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin System Inhibitors for the Prevention of Atrial Fibrillation Recurrence After Ablation ― A Meta-Analysis ―

Abstract: Background: Atrial fibrillation (AF) recurrence remains a tricky problem in patients undergoing ablation. This meta-analysis aimed to summarize the current literature to clarify whether renin-angiotensin system inhibitors (RASIs) prevent AF recurrence after ablation. Methods and Results: Relevant studies were searched on Pubmed and EMBASE through December 2019. Pooled relative risk (RR) of AF recurrence was calculated. Subgroup analyses according to study design, race, and follow-up duration were further perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Nineteen studies 7,14–31 reported the effect of RASIs on AF recurrence after ablation. The results showed that the recurrence rate of AF in subjects who received RASIs was lower than that of subjects who did not receive RASIs [RR = 0.85, 95% CI (0.72–0.99), P = 0.03] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies 7,14–31 reported the effect of RASIs on AF recurrence after ablation. The results showed that the recurrence rate of AF in subjects who received RASIs was lower than that of subjects who did not receive RASIs [RR = 0.85, 95% CI (0.72–0.99), P = 0.03] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that RASIs, including angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB), can prevent left atrial fibrosis and reverse atrial remodeling processes, reducing the occurrence of atrial fibrillation. 2 The world's first angiotensin receptor neprilysin inhibitor (ARNI)-SV, has antihypertensive, vasodilatory, and natriuretic effects and has accumulated much evidence in the treatment of heart failure and hypertension. 3,4 Although the pathophysiology of atrial fibrillation is not yet fully understood, an increasing number of prospective randomized controlled trials (RCTs) have confirmed that atrial fibrillation catheter ablation is superior to drug therapy in maintaining sinus rhythm and significantly improves symptoms and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this study, various studies have explored the effect of drugs on AF recurrence after ablation. One meta-analysis showed that the combined relative risk of AF recurrence in patients with RAAS inhibitors after ablation was 0.83 (95% CI: 0.70–0.98, p = 0.028), however, most studies that fulfill the inclusion criteria did not set a control group ( 47 ). Statins were found to reduce the recurrence of AF in the pooled randomized control trials, but not in all included studies ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The atrial electrical and structural remodeling are the core part of AF, and the activation of the renin-angiotensin-aldosterone system (RAAS) contributes to atrial remodeling [ 25 ]. Conversely, studies have demonstrated that renin-angiotensin system inhibitors can delay heart remodeling in patients with AF [ 26 ] and prevent recurrence of AF after ablation [ 27 ]. So, GSEA indicated that those gene sets in AF patients were primarily involved in cardiac muscle, immune, and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%